Nitrogen-doped carbon coated TiO2 nanocomposites as anode material to improve cycle life for lithium-ion batteries - Tan, Lei; Pan, Lei; Cao, Chengying; Wang, Baofeng; Li, Lei (Journal of power sources, 2014)
Anatase TiO2 has attracted much attention as a safe anode material for lithium-ion battery applications, due to its low electronic conductivity and severe aggregation during Li+ insertion/extraction processes, the practical application of the anatase TiO2 is still hindered by poor long-term cycling stability. In order to improve the cycling performance of lithium-ion batteries, a uniform thin nitrogen-doped carbon layer with a thickness of 3–6nm is successfully coated on the surface of the anatase TiO2 nanoparticles by using polydopamine as carbon precursor. Compared with the pristine TiO2 electrode, the carbon coated TiO2 nanocomposites electrodes show very good capacity retention and cycling performance. •Polydopamine used as carbon precursor to prepare carbon coated TiO2 composite.•The effect of the carbon layer thickness of the lithium-ion battery is investigated.•The optimized thickness of the carbon layer is about 4–5nm.•The lithium-ion battery using carbon coated TiO2 shows good cyclability.